2008
DOI: 10.1038/nmeth.1269
|View full text |Cite
|
Sign up to set email alerts
|

Intravital imaging of metastatic behavior through a mammary imaging window

Abstract: We report a technique to evaluate the same tumor microenvironment over multiple intravital imaging sessions in living mice. Individual tumor cells expressing photoswitchable proteins in an orthotopic mammary carcinoma are optically marked and followed for extended times through a Mammary Imaging Window (MIW). We demonstrate, for the first time, that two distinct microenvironments in the same orthotopic mammary tumor affect differently the invasion and intravasation of tumor cells. KeywordsTumor microenvironmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
342
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(348 citation statements)
references
References 15 publications
4
342
1
Order By: Relevance
“…We previously observed that tumor cell migration and invasion in vivo occurs more frequently near blood vessels (3,31). Therefore, we examined tumor cell Golgi-nucleus alignments as a function of blood vessel distance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously observed that tumor cell migration and invasion in vivo occurs more frequently near blood vessels (3,31). Therefore, we examined tumor cell Golgi-nucleus alignments as a function of blood vessel distance.…”
Section: Discussionmentioning
confidence: 99%
“…2P microscopy and intravital imaging procedure were preformed as described previously (5). The primary tumor was surgically exposed as described (31). Tumor cell polarization analysis was performed at 870 nm; and Z-stacks were captured at 2 ÎŒm steps over a Z-axis distance of 40 ÎŒm.…”
Section: Methodsmentioning
confidence: 99%
“…Despite progress in characterizing these vessels (18,19), it is not clear whether tumor cells require abnormal blood vessels to intravasate and how tumor cells and other factors in the tumor microenvironment (e.g., macrophages) contribute to vessel remodeling. Although in vivo imaging studies in animals have demonstrated the highly dynamic interaction between tumor and endothelial cells (9,10,12,20), quantitation of, or control over, vessel permeability and tumor microenvironmental factors is challenging. On the other hand, studies employing transwell inserts (21) that allow for manipulation of tumor-endothelial interactions do not enable visualization of intravasation events in real-time or precise control over cell-cell distance and growth-factor gradients.…”
mentioning
confidence: 99%
“…breast imaging) and minimally invasive imaging devices promise the translation of such tools into clinic [5]. Live cell and intravital microscopy (IVM) are other powerful optical imaging technologies, which are closing the gap between in vitro and in vivo assays by providing molecular information in high resolution [14,15]. Ideally, a comprehensive preclinical imaging platform consists of live cell microscopy, IVM and macroscopic imaging for whole animal imaging (fluorescence and bioluminescence).…”
Section: Optical Molecular Technologies Used In Drug Discovery (A) Tamentioning
confidence: 99%